LCA/LCC analysis of starting-lighting-ignition lead-acid battery in China - Ma, Yongxi; Yu, Shuao; Wang, Juanli; Yu, Wei (PeerJ, 2018)
Background China has the largest lead–acid battery (LAB) industry and market around the world, and this situation causes unavoidable emissions of Pb and other pollutants. Methods On the basis of a field survey on a starting–lighting–ignition (SLI) LAB plant in Zhejiang Province, this study applies life cycle assessment (LCA) and life cycle costing (LCC) methods to assess the environmental impacts and environment-related costs derived from the LAB industry during the life phases, including material preparation, battery assembly, transportation, and regeneration of the plant. Results Material preparation and regeneration phases contribute 3.4 and 42.2 g to Pb emission, respectively, and result in 3.29 × 108 CHY of environmental cost for each function unit (1 KVA h LAB capacity). The material preparation phase is the largest mass contributor to global warming potential (GWP, 97%), photo-chemical oxidation potential (POCP, 88.9%), and eutrophication potential (EP, 82.5%) and produces 2.68 × 108 CHY of environmental cost. Discussion Decision makers in the Chinese LAB industry should replace the pyrogenic process in smelting with the use of clean energy, increase the lead recovery rate while producing the same capacity of LABs, and develop new technologies to reduce heavy metal emission, especially in the regeneration phase.
Keywords: Life cycle costing; Life cycle assessment; Lead-acid battery; Environmental impact